Sulung The intersection of community cultural and mental health facility - Nunez, Alexandra Louise J.; Silvestre, Jose Danilo (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
This study explores the architectural translation for a model of community-based mental health in the context of San Fernando, Pampanga. In order to keep up with the demands made of its people, there is a need to improve the mental health facilities in the area. This can be done through the community-based approach that integrated the community into the healing of the individual. In San Fernando, Pampanga, this can be accomplished by using their cultural arts as a proponent to the process. Hence, culturally-based healing enables individual and collective mental health through the intersection of artistic and psychiatric spaces that implements the principles of community-building and community-based recovery. The result is an architecture that functions as a venue for 5 principles of community-building: collaboration and partnership and learning.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Mental health facilities; Mental health facilities -- Pampanga -- Philippines